TRANSFORMASI PENDIDIKAN MATEMATIKA DI ERA TEKNOLOGI: KAJIAN FILSAFAT TENTANG IMPLIKASI IPTEK - Susanti, Ade; Jainuri, Muhammad; Asyhar, Rayandra (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The transformation of mathematics education in the technological era has presented significant new challenges and opportunities in the learning process. The main problems faced include unequal access to technology, lack of teacher training, and resistance to changes in traditional teaching methods. To understand the impact and implications of this transformation, this study uses a literature review method that includes a variety of sources, including journal articles, books, and recent research reports. The subjects analyzed included various technological tools used in mathematics education, such as interactive software and online learning platforms, as well as pedagogical approaches that support technology integration. The analysis results show that the application of technology in mathematics education can improve students' understanding of concepts, interactivity, and engagement and provide better accessibility to learning resources. However, challenges such as lack of adequate training and access gaps remain obstacles that must be addressed. The conclusion of this study emphasizes the importance of continuous support for teachers and students to maximize the potential of technology in education. With the right approach, this transformation can create a more inclusive and effective learning environment, preparing students to face the challenges of an increasingly digital world